The intersectoriality in the public policies networks to consolidate the rights guarantee system: what do we learn in these 30 years of child and adolescent Statute? (Emancipação, 2020)
This article addresses the issue of the intersectoriality building of process in public policies networks. These networks are a condition for the Rights guarantee system (RGS) to offer a comprehensive protection for Brazilian child. It starts with premises established in the Statute of child and adolescent so that the RGS is the result of an agreed action and in complementary between public policies. However, this result sought is in contradiction with the instrumental rationality that organizes social production and reproduction in the bourgeois society. Against this background, the text follows was prepared based on results of field research and aims to demonstrate how it is possible to challenge the fragmentary logic of this rationality to build experiences of implementing public policies based on the logic of articulation and the collective agreement to design institutional formats for the provision of services that advance the realization of guarantee of fundamental rights. For this demonstration of viability the structuring experience of the Social Protection Intersectoral Network (RIPS) of Toledo - PR was used.
Keywords: Intersectoriality, Networks, Public Policies, Statute, RGS